BLAST LUNG INJURY: OUR EXPERIENCE AT A TERTIARY CARE MILITARY HOSPITAL - Ahmed Mujadid Burki (Army Medical College Rawalpindi, 2021)
Objective: To study the management and mortality in patients with blast lung injury at a tertiary care military hospital.